2018
DOI: 10.1002/ece3.4252
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the importance of the structure of ecological networks under an environment‐dependent framework

Abstract: A major quest in network and community ecology has been centered on understanding the importance of structural patterns in species interaction networks—the synthesis of who interacts with whom in a given location and time. In the past decades, much effort has been devoted to infer the importance of a particular structure by its capacity to tolerate an external perturbation on its structure or dynamics. Here, we demonstrate that such a perspective leads to inconsistent conclusions. That is, the importance of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…The same logic applies to ecological networks, as they are not merely the product of internal dynamical processes but also of the external environmental conditions [1,4]. In other words, the architecture of a network is much less useful without knowing the environmental pressures acting upon a community [30]. Following this rationale, we have confirmed that antagonistic and mutualistic communities cannot be differentiated using network metrics alone, but this differentiation becomes possible by adding environmental information.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The same logic applies to ecological networks, as they are not merely the product of internal dynamical processes but also of the external environmental conditions [1,4]. In other words, the architecture of a network is much less useful without knowing the environmental pressures acting upon a community [30]. Following this rationale, we have confirmed that antagonistic and mutualistic communities cannot be differentiated using network metrics alone, but this differentiation becomes possible by adding environmental information.…”
Section: Discussionmentioning
confidence: 52%
“…In other words, ignoring temperature variability is throwing out the opposing and predictable patterns of network architectures along environmental gradients [21,32]. Thus, we strongly believe that ecological networks should be analyzed under an environment-dependent approach [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that ours is just one possible way to capture the stability contribution of a link. Although other definitions could be used to measure different properties of community stability [32,33], we chose the feasibility approach to avoid constraints on the choice of parameters and type of perturbations that most stability metrics impose [4,34]. Feasibility largely avoids these issues by considering all possible sets of parameters and how these parameters can be changed by perturbations in any direction, thus allowing for a more generalisable and consistent metric of dynamic importance that is comparable across different networks (see Methods).…”
Section: Relationship Between Link Vulnerability and Link Feasibilitymentioning
confidence: 99%
“…Were such an extreme event to occur 380 when the network is less connected, less nested, and more specialized, its consequences might be 381 more severe. Thus, cumulative networks may overlook a relevant temporal scale for 382 understanding network robustness (or other aspects of community dynamics: e.g., Saavedra et al 383 2016a, b; Cenci et al 2018). However, we stress that many responses to disturbance are likely to 384 play out over time scales longer than weeks.…”
mentioning
confidence: 99%